Membangkitkan Sektor Usaha Di Tengah Pandemi Covid-19 Kabupaten Bantul - Herlianto, Didit (Jurnal Riset Daerah, 2020)
The business sector recovery program in the middle of the Covid-19 Pandemic has been carried out by both the central and regional governments or other empathy parties, but studies on the business sector recovery model in the middle of the Pandemic are still very minimal. Therefore, it is necessary to design a model for overcoming the impact of a pandemic on the sustainability of the business sector. This article is only a draft of the business sector recovery model in the middle of the Pandemic and has not been applied in field research. Relevant to this, research is needed. The purpose of this study was to determine the positive and negative effects of Pandemic Covid-19 on the business sector in Bantul Regency. From this impact, it will be known the need to revive the business sector. The data used in this study are primary data sourced from respondents' answers and the sampling technique used is purposive sampling. Where this research analysis is descriptive and in operational data analysis adopts the Root Cause Analysis (RCA) technique. With the recovery program based on findings in the field, a model can be drawn up on the distribution of aid for the recovery of the Bantul district business sector in new normal or new lifestyles that are adapted to Pandemic Covid-19. The recovery program should involve various related institutions, so that the handling will be comprehensive. It is hoped that the results of this study can be used as a reference in recovering and generating business sectors in the middle of the Covid Pandemic 19 Bantul Regency. In the long run, this model is expected to serve as a model for the recovery of the business sector, if identical conditions occur again in the future.